Welcoming visiting priest or not: Canon 903 - Espelage, Arthur J. (CLSA advisory opinions, 2001-2005, 2001)
Invited to celebrate and preach at a 50th wedding anniversary at a regularly scheduled Saturday afternoon Eucharist in a diocese where he was but is not currently assigned, a religious priest received forms from the diocese to be filled out by his major superior and the diocesan ordinary of his current assignment attesting that the priest is neither an untreated alcoholic or substance abuser nor an admitted, nor accused, nor proven sex abuser, nor a sexual predator. The forms needed to be completed by the diocesan and religious ordinary in order that the "host" diocese could authorize the visiting priest's participation at the anniversary mass. Do you care to comment?